If a=-1+root3i/2,b=-1-root3i/2 then show that a²=b and b²=a.
Answers
Answered by
4
Hence we have show that
and ![b^2=a b^2=a](https://tex.z-dn.net/?f=b%5E2%3Da)
Step-by-step explanation:
Given that and
To show that
and ![b^2=a b^2=a](https://tex.z-dn.net/?f=b%5E2%3Da)
- Let us first show that
Take LHS
Substitute the value of a in the above expression we get
( by using the property
)
( by using the identity
here a=-1 and b=
)
( by using
)
Therefore hence proved
- Let us show that
Take LHS
Substitute the value of a in the above expression we get
( by using the property
)
( by using the identity
here a=-1 and b=
)
( by using
)
Therefore hence proved.
Similar questions
Computer Science,
7 months ago
India Languages,
7 months ago
Physics,
7 months ago
Physics,
1 year ago
Chemistry,
1 year ago